(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the significance of spiritual education within both Eastern and Western cultures, highlighting the historical foundations and contemporary interpretations of moral and ethical upbringing. It examines how spiritual values shape individual character and societal norms in different cultural contexts. The paper also analyzes the challenges and opportunities presented by globalization in harmonizing traditional spiritual teachings with modern educational frameworks. By comparing the approaches to spiritual education in the East and West, the study aims to offer insights into fostering a holistic development that integrates ethical, emotional, and intellectual growth in today’s diverse societies.